Hydrophobic superparamagnetic FePt nanoparticles in hydrophilic poly(N-vinylcaprolactam) microgels: a new multifunctional hybrid system. Issue 6 (26th January 2017) - Wiemer, K.; Dörmbach, K.; Slabu, I.; Agrawal, G.; Schrader, F.; Caumanns, T.; Bourone, S. D. M.; Mayer, J.; Steitz, J.; Simon, U.; Pich, A.
Abstract : We report the synthesis of a new multifunctional colloidal hybrid system consisting of thermoresponsive amphiphilic biocompatible poly( N -vinylcaprolactam) microgels loaded with hydrophobic superparamagnetic FePt nanoparticles (NPs). Abstract : We report the synthesis of a new multifunctional colloidal hybrid system consisting of thermoresponsive amphiphilic biocompatible poly( N -vinylcaprolactam) microgels loaded with hydrophobic superparamagnetic FePt nanoparticles (NPs). In the first step, water swellable poly( N -vinylcaprolactam) microgels were mixed with hydrophobically coated sub-10 nm superparamagnetic FePt NPs in a tetrahydrofuran (THF) solution. In the second step, changing the surrounding solvent from THF to water forces the FePt NPs to migrate into the amphiphilic microgels. These new hybrid microgels (i) are colloidally stable in water and their thermo-responsive properties in terms of volume phase transition are retained, (ii) exhibit superparamagnetic characteristics introduced by FePt NPs, (iii) show a drastically reduced cytotoxicity compared to water-soluble FePt NPs of similar size, as known from the literature. This makes the new hybrid microgels suitable e.g. as biocompatible containers for drug delivery or for imaging.